2022
DOI: 10.3390/metabo12080677
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Severe Osteoarthritis in a Spanish Population of Women Compared to Healthy and Osteoporotic Subjects

Abstract: Bone pathologies such as osteoporosis (OTP) and osteoarthritis (OA) are rising in incidence with the worldwide rise in life expectancy. The diagnosis is usually obtained using imaging techniques such as densitometry, but with both being multifactorial diseases, several molecular mechanisms remain to be understood. Metabolomics offers the potential to detect global changes which can lead to the identification of biomarkers and a better insight in the progress of the diseases. Our aim was to compare the metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Of the remaining 44 studies, 1 was excluded due to incomplete information, 3 were excluded due to no access to the full text, and 27 were not eligible according to our criteria. At last, 13 studies [38][39][40][41][42][43][44][45][46][47][48][49][50] were included for qualitative synthesis. Of those 13 studies, 4 studies [38,44,47,48] with 495 participant (242 in OA group, 253 in healthy control group) were recruited into the meta-analysis.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the remaining 44 studies, 1 was excluded due to incomplete information, 3 were excluded due to no access to the full text, and 27 were not eligible according to our criteria. At last, 13 studies [38][39][40][41][42][43][44][45][46][47][48][49][50] were included for qualitative synthesis. Of those 13 studies, 4 studies [38,44,47,48] with 495 participant (242 in OA group, 253 in healthy control group) were recruited into the meta-analysis.…”
Section: Literature Searchmentioning
confidence: 99%
“…All of the included studies were published between 2009 and 2022 and designed as case-control studies. Eight studies [43][44][45][46][47][48][49][50] were reported in English and five studies [38][39][40][41][42] in Chinese. The participants were recruited from Spain [46], the UK [43], Estonia [47], Canada [44] and China [38][39][40][41][42]45,[48][49][50].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings suggest that diabetes mellitus combined with OP will further lead to significant changes in amino acid metabolism and energy metabolism, such as tricarboxylic acid cycle products and various branched-chain amino acids ( 75 ). OP combined with osteoarthritis will further alter the phospholipid precursors, energy metabolism and amino acid metabolites of OP ( 82 ). In addition, lipoprotein and amino acid metabolites are significantly different when OP is associated with atherosclerosis ( 83 ).…”
Section: Metabolomics In Op Pathogenesis Researchmentioning
confidence: 99%
“…There are many other factors that could affect bone mineral density, such as age, exercise, body weight, and serum mineral level [16]. As we all know, age can significantly affect bone mineral density.…”
Section: Introductionmentioning
confidence: 99%